Squareflower, Paronychia erecta: SGEB-75-18/SG179, 9/2018 - Miller, Debbie; Thetford, Mack; Verlinde, Chris; Campbell, Gabriel; Smith, Ashlynn (EDIS, 2018)
Squareflower is found in beach dunes, coastal grasslands, and scrub. This plant is an endemic restricted to the coastal Panhandle of Florida, counties west of the Big Bend region, and west to Louisiana. The square outline of the inflorescence is unique and makes squareflower a desirable plant for coastal landscapes. https://edis.ifas.ufl.edu/sg179 This publication is derived from information in SGEB-75/SG156, Dune Restoration and Enhancement for the Florida Panhandle, by Debbie Miller, Mack Thetford, Christina Verlinde, Gabriel Campbell, and Ashlynn Smith. https://edis.ifas.ufl.edu/sg156.